1994
DOI: 10.1021/ja00096a013
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Mechanistic Analysis of Dinucleotide and Oligonucleotide Formation from the 5'-Phosphorimidazolide of Adenosine on Na+-Montmorillonite

Abstract: The rate constants for the condensation reaction of the 5'-phosphorimidazolide of adenosine (ImpA) to form dinucleotides and oligonucleotides have been measured in the presence of Na(+)-volclay (a Na(+)-montmorillonite) in pH 8 aqueous solution at 25 degrees C. The rates of the reaction of ImpA with an excess of adenosine 5'-monophosphoramidate (NH2pA), P1,P2-diadenosine 5',5'-pyrophosphate (A5'ppA), or adenosine 5'-monophosphate (5'-AMP or pA) in the presence of the montmorillonite to form NH2pA3'pA, A5'ppA3'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 9 publications
6
78
0
1
Order By: Relevance
“…However, the very limited studies in prebiotic chemistry relevant to this hypothesis have not uncovered any highly regiospecific reactions. Ferris and his coworkers (25,26) have shown that montmorillonite catalyzes the oligomerization of adenosine 5Ј-phosphorimidazolide and leads to the formation of oligomers substantially enriched in 3Ј-5Ј phosphodiester bonds. However, the regiospecificity is only about 80%, less than the regiospecificity in favor of 2Ј-5Ј-bonds of the uncatalyzed reaction.…”
Section: Nonenzymatic Metabolismmentioning
confidence: 99%
“…However, the very limited studies in prebiotic chemistry relevant to this hypothesis have not uncovered any highly regiospecific reactions. Ferris and his coworkers (25,26) have shown that montmorillonite catalyzes the oligomerization of adenosine 5Ј-phosphorimidazolide and leads to the formation of oligomers substantially enriched in 3Ј-5Ј phosphodiester bonds. However, the regiospecificity is only about 80%, less than the regiospecificity in favor of 2Ј-5Ј-bonds of the uncatalyzed reaction.…”
Section: Nonenzymatic Metabolismmentioning
confidence: 99%
“…O mecanismo de catálise da polimerização de nucleótidos por argilas montemorilonite não é totalmente conhecido, mas o desempenho do silício pode não ser relevante. 72,[74][75][76][77] …”
Section: Polimerização De Ribonucleótidosunclassified
“…As noted above, the rate constant for the montmorillonite-catalysed oligomerization of 5 0 -phosphorimidazolide of adenosine is 100-1000 times greater than the rate of its hydrolysis. Hydrolysis is the main reaction product in the absence of montmorillonite along with a few percentage of dimers, where the rate constant of oligomer formation is only 10 times that of hydrolysis (Kawamura & Ferris 1994;Kanavarioti 1997).…”
Section: Why the Origin Of Life Required Catalysts (A) Formation Of Bmentioning
confidence: 99%